Governance of the Central Market in Kota Selatan Subdistrict, Gorontalo City After Revitalization - Mohamad Taufik M. Pandi; Sukarman Kamuli; Roni Lukum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aimed to examine the governance of the Pasar Sentral in Kota Selatan Subdistrict, Gorontalo City, after its revitalization. The background of this research stems from the market's previous condition, which was rundown and disorganized, prompting the Gorontalo City Government to carry out a revitalization project. However, despite the revitalization efforts, issues such as low visitor numbers, limited access to clean water, as well as drainage and sanitation problems, remain major concerns. This research used a qualitative approach with a descriptive method. Data were collected through observation, interviews with representatives from the Department of Industry and Trade, market vendors, and the community, as well as documentation. The findings indicate that market governance includes planning, implementation, and supervision in accordance with Henry Fayol's management theory. Nevertheless, challenges persist in the implementation, particularly regarding facility management, the retribution system, and the involvement of vendors in decision-making processes. In conclusion, the revitalization has not fully resolved the market's underlying problems. Strengthened coordination between the government and market stakeholders, along with improvements to supporting infrastructure, are needed to transform the market into a more attractive shopping center for the community.